Investigation of Potential Activity of Some Organic Compounds and Antiviral Drugs Against COVID-19 Based on Molecular Docking - Pal, T. K.; Paul, S.; Hossen, J. (Journal of Scientific Research, 2022)
The current outbreak of the COVID-19 threatens public health worldwide, and WHO declares this as a global pandemic. Effective oral drug therapy against coronavirus did not discover yet. In order to find out an effective drug, we docked 23 compounds within the active site of 6LU7 protein of coronavirus. Among all, some antivirals exhibited very promising results against coronavirus and may be considered as a potential drug for treating COVID-19 disease. Molecular docking study revealed that isovitexin and apigenin found from nishinda (Vitex sp.) as well as our newly prepared compound (E)-4-((3,5-dibromo-2-hydroxybenzylidene)amino)-N-(5-methylisoxazol-3-yl)benzenesulfonamide showed exce-llent activity as compared to danoprevir, lopinavir, remdesivir and ritonavir. Isovitexin showed a binding affinity of -8.00 kcal/mol, whereas the binding affinity of sulfonamide compound with the coronavirus protein was -7.30 kcal/mol, which was relatively high compared to other antiviral drugs. Besides, the synthesized sulfonamide compound's absorption, distribution, metabolism, excretion, and toxicity profiles were also carried out. The compound showed excellent drug-like properties and percentage of human oral absorption. Moreover, it was found to be safe for the human body in toxicological risk assessment.